Easy to do family DIY reflexology kit / Long Chiau Ming … [et al.] - Chiau Ming, Long; Shaharuddin, Shazwani; Yee Chang, Soh; Abdul Hameed, Mohammed; Siew Kuan, Chua (Research Innovation Business Unit, 2014)
Reflexology is an ancient art of healing that the general public can learn to perform personally or on their loved ones in the comfort of the house. Studies show that reflexology is effective in controlling migraine, body aches, back pain or even stroke and diabetes mellitus. Reflexology is different from foot massage because the former is a holistic (body, mind and soul) form of healing. Reflexology is very useful to induce deep relaxation which helps to relieve tension and activate the body’s natural healing power. It is especially true when our body is experiencing stress and tired making it easier for us to fall ill. Furthermore, by practicing reflexology, we could fine tune and stabilise our emotional, spiritual and mental as well as physical state. Like any other healthy exercise, its effects are optimised when it is performed regularly. The main aim of introducing this innovative DIY Reflexology Kit is to teach the general public the correct technique to perform reflexology. This kit consists of a foot massager stick, warming up roller, thigh massager, bespoke socks with mapping of the reflex points as well as a fully illustrated guide book. The user could learn where the reflexes are on the feet that correspond to every limb, organ and hormonal gland. The theoretical concept is our body is divided into a system of longitudinal and transverse zones. The transverse zones, for example, divide the areas of our feet into zones that correspond to our head and neck, chest, abdomen and the pelvis area. Another important concept is the reflex areas in the left foot represent the left half of the body and vice versa. The user could relieve neck tension by applying pressure to the joints or “necks” of the eight little toes. If the user experiences tension in one area of the neck, he/she will feel tension or slight discomfort in the corresponding toes. Alternatively, because the entire head is represented in our two big toes, the user could apply pressure to the big toes to relieve headache tension. Another must-try reflex points is the instep (the non-weight bearing area on the bottom of the foot) to enhance the gut functions such as digestion and gastric. The user also could apply pressure to the lung’s reflex points located on the ball of the foot to reduce insomnia (inability to sleep) due to breathing difficulties. Apart from that, the user could prevent restless leg syndrome by working on the heart reflexes which will stimulate the circulation system. This innovation contributes towards Agenda 9 of National Key Economic Areas (NKEA) on healthcare because the kit could help to produce local talents to perform reflexology. This kit could also lead to the development of a more advanced automation system to introduce reflexology which has higher commercialisation values. Furthermore this kit definitely could enhance the quality of life in terms of diseases control and improved body conditions. In view of the National Policy on Traditional and Complementary Medicine, this kit could provide safe and healthy reflexology therapy.